Adopting Excel-Macro and POM-QM Automation System to Enhance Operational Efficiency in an Herbal MSME - Yakobus Saktono Adi (Dinasti Review, 2026)
This study designs and implements a production automation system using Excel-Macro integrated with POM-QM to improve production and time efficiency in the micro-scale herbal enterprise Sekar Utami Toga, located in South Tangerang, Banten, Indonesia. Building upon previous research on linear programming optimization, this study integrated the optimization model within an automated workflow. A quantitative descriptive pre-post design was used to compare production performance before (2024) and after (2025) automation. Data were collected through observation, time studies, interviews, and production records. The findings reveal substantial performance improvements: total output increased by 42.5%, profit margins rose by 27%, and production capacity utilization expanded by 34.6%. Data entry errors decreased by 90%, and documentation time reduced by 98.9%. Efficiency ratio analysis indicated moderate gains of 0.11% in production efficiency and 0.07% in time efficiency. Although relatively small, these improvements are significant for MSMEs due to higher productivity and output volume. A paired t-test confirmed a statistically significant enhancement in efficiency (t (7) = 4.08, p = 0.004 < 0.05). The study concludes that low-cost automation using Excel-Macro and POM-QM can effectively enhance operational efficiency, accuracy, and decision-making, offering a practical model for MSME digital transformation in Indonesia’s herbal industry.